An improved supervisory protocol for automatic selection of routing protocols in environment-aware vehicular ad hoc networks. (November 2018) - Wahid, Ishtiaq; Ikram, Ata Ul Aziz; Ahmad, Masood; Ullah, Fasee
With resource constraint's distributed architecture and dynamic topology, network issues such as congestion, latency, power awareness, mobility, and other quality of service issues need to be addressed by optimizing the routing protocols. As a result, a number of routing protocols have been proposed. Routing protocols have trade-offs in performance parameters and their performance varies with the underlying mobility model. For designing an improved vehicular ad hoc network, three components of the network are to be focused: routing protocols, mobility models, and performance metrics. This article describes the relationship of these components, trade-offs in performance, and proposes a supervisory protocol, which monitors the scenario and detects the realistic mobility model through analysis of the microscopic features of the mobility model. An analytical model is used to determine the best protocol for a particular mobility model. The supervisory protocol then selects the best routing protocol for the mobility model of the current operational environment. For this, EstiNet 8.1 Simulator is used to validate the proposed scheme and compare its performance with existing schemes. Simulation results of the proposed scheme show the consistency in the performance of network throughout its operation.